PENYELESAIAN KONFLIK PERTANAHAN PADA KAWASAN PARIWISATA LOMBOK (STUDI KASUS TANAH TERLANTAR DI GILI TRAWANGAN LOMBOK) - Zainal Asikin (Jurnal Dinamika Hukum, 2014)
This research is aimed at exploring an appropriate solution for various conflicts in land use, particularly in optimizing the utilization of the neglected land in Gili Terawangan, Lombok Island.  This solution is required to avoid potential horizontal conflicts among people, companies and government since 1993. Conflict over land in Lombok Island in general and Gili Terawangan particularly shows several factors; first, the wrong policy in the area of land (especially in tourist areas); second, the infirm attitude of the Party and the Government Land Office in the enforcement of laws; third, the jealousy of Gili Terawangan natives as cultivators; fourth, less responsibility employers (who acquire cultivating right); fifth, the absence of law protection for Gili Terawangan natives; sixth, the arrogant attitude of law enforcement officers. The comprehensive and final resolution to the conflicts of land use could only be achieved if: (i) the people, who already control and use or manage the land from time to time, are provided certainty on managing and optimizing the land based on the principles of welfare, justice, equity, efficiency and sustainability; (ii) the selection and determination of the companies that will be granted the right to cultivate (HGU) and the right to build (HGB) should be conducted based on the transparent principle. In this respect, the government could establish an independent team that involves all components of society and higher education.Key words: land dispute, tourism area, agrarian law.